2018
DOI: 10.1021/acsami.8b00833
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Tetrahedral DNA Nanostructures Promote Neural Stem Cell Proliferation and Neuronal Differentiation

Abstract: Stem cell-based therapy is considered a promising approach for the repair of nervous tissues. Neural stem cells (NSCs) cannot proliferate or differentiate efficiently; hence, different biomaterials have been explored to improve NSC proliferation and differentiation. However, these agents either had low bioavailability or poor biocompatibility. In this work, our group investigated the effects of tetrahedral DNA nanostructures (TDNs), a novel DNA biological material, on the self-renew and differentiation of neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
126
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 109 publications
(131 citation statements)
references
References 58 publications
5
126
0
Order By: Relevance
“…Therefore, TDNs possess excellent structural stability, mechanical rigidity and modification versatility . Previous studies of TDNs have shown that different cells could internalize TDNs, and then TDNs exerted influence on the cells’ biological behaviours under certain conditions . For instance, TNDs could maintain the chondrocyte phenotype, promote chondrocyte proliferation and accelerate dental pulp stem cells osteo/odontogenic differentiation .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, TDNs possess excellent structural stability, mechanical rigidity and modification versatility . Previous studies of TDNs have shown that different cells could internalize TDNs, and then TDNs exerted influence on the cells’ biological behaviours under certain conditions . For instance, TNDs could maintain the chondrocyte phenotype, promote chondrocyte proliferation and accelerate dental pulp stem cells osteo/odontogenic differentiation .…”
Section: Introductionmentioning
confidence: 99%
“…Tetrahedral framework nucleic acids (tFNAs) are synthesized by four isometric single‐stranded DNAs through a simple, rapid, and reliable process, which have been identified as 3D DNA nanostructures with a stable structure and superior mechanical properties . Many biological functions can be affected after tFNAs are transported into cells, including osteogenic differentiation, nerve tissue regeneration, anti‐inflammatory, and antioxidant effects . In addition, tFNAs can be easily formulated as eye drops, which can be very convenient for experimental research and clinical use in the future.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we encourage developments in disciplines which have not heavily utilized designer DNA nanostructures. A discipline in which we have seen some initial work, but believe can be further developed, is the control of stem cell behavior/differentiation . For example, multiple ephrin molecules (a protein ligand) may interact with multiple Eph receptors to induce stem cell differentiation; placing this molecule at different spacing may induce different stem cell behaviors ( Figure ).…”
Section: Conclusion and Outlooksmentioning
confidence: 99%